If f(x) = 3x2 – 2x + 4 and g(x) = 5x2 + 6x – 8, find (f + g)(x).
![If fx 3x2 2x 4 and gx 5x2 6x 8 find f gx class=](https://us-static.z-dn.net/files/de4/093e971a5d94a485e7c3121da852cba2.jpg)
Answer:
Option C is correct
[tex](f+g)(x)=8x^2+4x-4[/tex]
Explanation:
Given the function:
[tex]f(x) = 3x^2-2x+4[/tex]
[tex]g(x) = 5x^2+6x-8[/tex]
[tex](f+g)(x) =f(x)+g(x)[/tex]
Substitute the given values we have;
[tex](f+g)(x) = 3x^2-2x+4+5x^2+6x-8[/tex]
Combine like terms;
[tex](f+g)(x) = 8x^2+4x-4[/tex]
Therefore the value of [tex](f+g)(x)[/tex] is, [tex]8x^2+4x-4[/tex]